Hydrocarbon Generation Evaluation of Permo- Carboniferous Source Rocks in Qinggu-2 Well in Dongpu Depression, China - 朱炎铭 陈尚斌 兰晓东 王猛 方俊华 (Journal of earth science (Wuhan, China), 2010)
The Dongpu （东濮） depression is a Mesozoic subsidence and Cenozoic fault basin developed within the North China eraton. Since the deposition of Permo--Carboniferous hydrocarbon source rock, the depression has undergone many tectonic disturbances and uplifts. The source rocks have un- dergone nonuniform uplift, deformation, deep burying, and magmatism, and those led to an inter- rupted or stepwise evolution of the hydrocarbon source rocks in Qinggu （庆古）-2 well. We have investigated the history of burying, heating, and hydrocarbon generation of the Permo-Carboniferous hy- drocarbon source rocks not just on the basis of tectonic disturbance and deep burying, but also with new studies in apatite fission track analysis, fluid inclusion measurements, and the application of the numerical simulation of EASY%Ro. The heating temperature of the source rocks pulsated upward from Indosinian to Himalayan stages and reached a maximum during early Himalayan. This led to the stepwise increases of organic maturation and multiple stages of hydrocarbon generation. This study delineated the tectonic stages, maturity evolved ranges, and the intensity of hydrocarbon generation of Permo-Carboniferous source rocks in Qinggu-2 well. The hydrocarbon gen- eration mainly occurred during Indosinian and early Himalayan. The early Himalayan stage hydrocarbon generation is the larger one, but the Dongying （东营） movement, which happened at the end of early Himalayan, may destroy the trapped oil and gas. Thereby, future exploration will need to pay more attention to the Dongying movement effect in Qinggu-2 well area, and it may get new breakthrough in Permo-Carboniferous oil and gas.